GE_GERICHTE P/26351/2023 vom 5. Mai 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ESCROQUERIE;USURE(DROIT PÉNAL);HONORAIRES;CONTRAINTE(DROIT PÉNAL);FAUX MATÉRIEL DANS LES TITRES | CPP.310; CP.146; CP.157; CP.251; CP.181